PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NHT (NUMBERED HEADS TOGETHER) BERBANTUAN MEDIA SIMULASI PHET TERHADAP AKTIVITAS BELAJAR DAN HASIL BELAJAR SISWA SMA DI JEMBER - Yopie Firmansyah; I Ketut Mahardika; Agus Abdul Gani (FKIP Universitas Jember, 2017)
Numbered Heads Together model with PhET simulation as media is one kind of learning model that has the same principle like inquiry which is emphasized at integrating knowledge actively between experience or prior knowledge and new knowledge by students's active role through learning process which is helped by PheT simulation as media at focusing step so students can find knowledge by them self. This research aims to review the difference of study results between students who were taught using Numbered Heads Together model with PheT simulation as media and the students who were taught using direct learning model that has usually been taught by a teacher in senior high school. The students's achievement contains cognitive, affective, and psychomotor. This design of research is an experimental research that has been done at the senior high school 1 Pakusari. Source of data was derived from the assessment by the observer and post-test. The conclusions of the research have got that Numbered Heads Together model with PheT simulation as media influenced the students's achievement in cognitive, affective, and psychomotor.